The competition : a novel - Clark, Marcia (Clark, Marcia. Rachel Knight novel., 2014)
While interviewing students in the aftermath of a school shooting in the San Fernando Valley, prosecutor Rachel Knight and Detective Bailey Keller realize the facts don't add up and the real killers may still be out there.